The genetics of breast and ovarian cancer - Welcsh, Piri (Henry Stewart Talks, 2007)
General cancer genetics, Tumor suppressor and oncogenes, Knudson's 'two hit' hypothesis, Genetic predisposition to breast and ovarian cancer, How much breast and ovarian cancer is inherited and the causes (genes responsible), Cancer risk in populations, Factors that affect penetrance, Mutation detection, Risk reduction and prevention strategies
Archived at 2017/11/11